Automatic Welding of Corrugated Steel Webs on Composite Box Girder with Corrugated Steel Webs - Yunfei Wu; Yingbo Zhu; Xiaoyong Chen; Shui Wan (Advances in Civil Engineering, 2024)
With the advancement of technology, automation in construction has gained great popularity in both the industrial and academic worlds to date, since it not only can improve construction efficiency and alleviate the request for intensive labor but also can improve construction quality by reducing human error. The composite box girder with corrugated steel webs (CBGCSW), a new type of composite bridge, has become popular and attracted considerable attention in the world. However, the welding of corrugated steel webs (CSWs) poses challenges on construction sites, primarily due to the considerable height of CSWs and also due to the complexity of construction environments of such composite structures, causing complications for welding personnel. In the context, based on the welding characteristics of CSW, this study proposes a direct rail-type mobile welding equipment for automatic welding of CSW to reduce the requirements for intensive labor and ensure welding quality. Three types of welding tests including lap welding, butt welding, and V-groove butt welding are carried out in this study by using this automatic welding method and manual method in order to verify the feasibility of the automatic welding method. The comparison between the two approaches shows that the quality of those specimens welded by the proposed straight rail welding equipment is significantly superior to the manual method: weld seams are smoother, the fish scale pattern is clear, and the texture is uniform. Furthermore, tensile experiments are performed on the welded specimens to further validate the welding capacity of such automated methods, indicating that the strength of the welded steel specimens operated by using the proposed straight rail welding mobile equipment can achieve good mechanical performance. Based on the experimental investigation, the direct-guided rail-type mobile welding equipment is applied to the on-site construction of CBGCSW. This study reveals that this automatic method not only can achieve a good welding quality and effect of CSWs but also improve efficiency and reduce the requests for intensive labor on construction sites.